Applying Bulldog Clamps to Prevent Stone Migration in Laparoscopic Upper Ureteral Stone Surgery - Basiri, Abbas; Sotoudeh, Mehdi; Ghaed, Mohammad Ali; Ghanbarizadeh, Saeed Reza (Jordan Medical Journal, 2024)
Background: Urolithiasis can be managed by endoscopic, laparoscopic, percutaneous, or open approaches. We introduce an effective and safe method for stone migration during laparoscopic ureterolithotomy. Description of Technique: We used laparoscopic intraperitoneal approach, with three ports. Stone is localized and the ureter occluded proximally and distally to the stone using bulldog clamps to minimize the risk of stone migration. Patients and Methods: Case 1 had a 15 mm left upper ureteral stone — refractory to ESWL. Case 2 had a 17mm right upper ureteral stone without previous stone procedure. Case 3 had a history of failed ESWL for a 17mm left upper ureteral stone. Results: Mean operation time was 55 minutes, mean hospital stay was two days, and SFR was 100%. No complications occurred during this minimally invasive surgery, either intra-operatively or post-operatively. Conclusion: This is a safe and effective maneuver, increasing the stone-free rate of the procedure, which facilitates stone surgery by releasing the surgeon’s hands and preventing stone migration.